Szkicowniki malarza Marcina Zaleskiego - Mostowicz-Kapciak, Ewa (Sztuka i Kultura, 2021)
The creative output of Marcin Zaleski, the most outstanding Polish landscape painter of his time, is known only fragmentarily due to enormous war losses. All the more valuable are his two sketchbooks preserved in the collection of Muzeum Narodowe (National Museum) in Warsaw. The books shed new light to the creative methods of the painter as well as the factors shaping his artistic attitude. The earlier of the sketchbooks is a testimony to the painter’s trip around Europe in 1829. It contains drawings bearing marks of the finished artworks. Vast vedutas or visions of monuments engulfed by Italian countryside allow to consider Zaleski a skillful drawing artist sensitive to nature and its luministic effects. The drawings constitute not just memories of the visited places, they record the shapes of interesting architectonic compositions, multiplied in the artist’s subsequent output in his oil paintings. Side by side with them one can come across rough sketches and even construction drawings as well as an array of notes documenting the artist’s activity as a theatre stage designer. There, we can also see a sketch of an optical device, which correlates with press reports of the time stating that Zaleski employed daguerrotype in his painting. The later one – the Polish sketchbook – contains rough drawings for the subsequent oil paintings. They depict landscapes and vedutas as well as the interiors of monuments. They allow for the reconstruction of Zaleski’s creative process: the lookout for the right frame, the description of weather phenomena, split-up drawings of more complex fragments of the view, employing sketching and optical equipment. The sketches made it possible to newly date some of the artwork as well as the very sketchbook itself for the year 1834. Thanks to the drawings it was possible to restore the link between Zaleski and a painting previously attributed to another artist. The sketchbook also contains rough drawings of the works considered lost.